THE IMPACT OF ARTIFICIAL INTELLIGENCE UTILIZATION IN MANAGERIAL OFFICE DECISION-MAKING ON BUSINESS ETHICS: A SYSTEMATIC LITERATURE REVIEW - Silaen, Abraham Lincoln Mangaratua Silaen; Manan, De Habib Habibul; Chaniago, Harmon (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study analyzes the role of Artificial Intelligence (AI) in supporting the managerial decision-making process, particularly in relation to business ethics. Technological advancements have significantly impacted the business world, especially in managerial decision-making. This study identifies the influence of AI on management, including work efficiency, reduced subjectivity, and business strategy optimization. The findings indicate that AI can effectively support office managerial activities. However, AI implementation also presents several ethical challenges, such as algorithmic bias, decision-making transparency, and data security concerns for both companies and customers. This study uses a qualitative-descriptive research design with a literature review approach. The literature review was conducted by collecting articles from journals indexed in Google Scholar and relevant to the research objectives in the last few years (2017–2024).